The Influence of Brand Awareness and Perceived Quality on Consumer Loyalty with Brand Equity as an Intervening Variable: Study at Consumer Oppo Smartphone in Palangka Raya City - Reza Raihansya; Meitiana Meitiana; Vivy Kristinae; Trecy E Anden (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Smartphone users in Indonesia are projected to reach 195.26 million by 2024. This has led to increased competition among smartphone vendors, causing each vendor to compete to either increase or maintain their market share. One of the most famous smartphone brands in Indonesia is Oppo, which ranks among the top 2 smartphones in Indonesia based on the top brand index. This research aims to gain a deeper understanding of smartphone marketing strategies in Indonesia and analyze several variables that show inconsistencies in the research results. This research employed a quantitative method with a sampling technique using the Lemeshow approach, resulting in a sample size of 100 respondents. The collected data was then processed using SmartPLS. The research results showed that brand awareness, perceived quality, and brand equity had a positive and significant influence on consumer loyality. Furthermore, in the mediation test, brand equity was able to mediate the influence between perceived quality and consumer loyality but failed to mediate the relationship between brand awareness and consumer loyality.